Editor's Choice – Post-operative Surveillance and Long Term Outcome after Endovascular Aortic Aneurysm Repair in Patients with an Initial Post-operative Computed Tomography Angiogram Without Abnormalities: the Multicentre Retrospective ODYSSEUS Study. (March 2022) - Geraedts, Anna C.M.; Mulay, Sana; Vahl, Anco C.; Verhagen, Hence J.M.; Wisselink, Willem; de Mik, Sylvana M.L.; van Dieren, Susan; Koelemay, Mark J.W.; Balm, Ron; ,; Balm, R.; Elshof, J.W.; et al.
Abstract : Objective: Lifelong imaging surveillance is recommended following endovascular aneurysm repair (EVAR). This study aimed to examine the association between adherence to post-operative surveillance and survival and secondary interventions in patients with an initial post-operative computed tomography angiogram (CTA) without abnormalities. Methods: All consecutive patients undergoing EVAR for intact abdominal aortic aneurysm (AAA) in 16 hospitals between 2007 and 2012 were identified retrospectively, with follow up until December 2018. Patients were included if the initial post-operative CTA showed no types I – III endoleak, kinking, infection, or limb occlusion. Discontinued follow up was defined as at least one 16 month period in which no imaging surveillance was performed. Primary outcomes were aneurysm related mortality and secondary interventions, and secondary outcome all cause mortality. Kaplan–Meier analysis was used to estimate survival, and Cox regression analyses to identify the association between independent variables and outcome. Sensitivity analyses were performed by varying the definition of continued yearly follow up. The study protocol was published (bmjopen-2019-033584). Results: 1 596 patients (552 continued, 1 044 discontinued follow up) were included with a median (interquartile range) follow up of 89.1 months (52.6). Cumulative aneurysm related, overall, and intervention free survival was 99.4/94.8/96.1%, 98.5/72.9/85.9%, and 96.3/45.4/71.1% at 1, 5, and 10 years, respectively. American Society of Anesthesiologists (ASA) classification (ASA IV hazard ratio [HR] 3.810, 95% confidence interval [CI] 1.296 – 11.198), increase in AAA diameter (HR 3.299, 95% CI 1.408 – 7.729), and continued follow up (HR 3.611, 95% CI 1.780 – 7.323) were independently associated with aneurysm related mortality. The same variables and age (HR 1.063 per year, 95% CI 1.052 – 1.074) were significantly associated with all cause mortality. No difference in secondary interventions was observed between patients with continued vs. discontinued follow up (89/552; 16% vs . 136/1044; 13%; p  = .091). Sensitivity analyses showed worse aneurysm related and overall survival in patients with continued follow up. Conclusion: Discontinued follow up is not associated with poor outcomes. Future prospective studies are indicated to determine in which patients imaging follow up can be safely reduced.